Preserving Neuronal Chemical Messengers: Heat Stabilization Versus Snap Freezing for Improved MALDI Mass Spectrometry Imaging of Brain Tissues - Salviati, Emanuela; Luptáková, Dominika; Nilsson, Anna; Shariatgorji, Reza; Campiglia, Pietro; Tjernström, Nikita; Roman, Erika; Andrén, Per E (Journal of neurochemistry, 2025)
One of the main challenges in analyzing chemical messengers in the brain is the optimization of tissue sampling and preparation protocols. Limiting postmortem time and terminating enzyme activity is critical to identify low-abundance neurotransmitters and neuropeptides. Here, we used a rapid and uniform conductive heat transfer stabilization method that was compared with a conventional fresh freezing protocol. Together with a selective chemical derivatization method and an optimized quantitation approach using deuterated internal standards, we spatially mapped neurotransmitters and their related metabolites by matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) in rat brain tissue sections. Although the heat stabilization did not show differences in the levels of dopamine, norepinephrine, and serotonin, their related metabolites 3,4-dihydroxyphenylacetaldehyde, 3,4-dihydroxyphenylacetic acid, homovanillic acid, 3-methoxy-4-hydroxyphenylacetaldehyde, dihydroxyphenylethyleneglycol, and 5-hydroxyindoleacetic acid were all significantly lower, indicating reduced neurotransmitter postmortem turnover ratios. Heat stabilization enabled detection of an increased number and higher levels of prodynorphin, proenkephalin, and tachykinin-derived bioactive neuropeptides. The low-abundant C-terminal flanking peptide, neuropeptide-γ, and nociceptin remained intact and were exclusively imaged in heat-stabilized brains. Without heat stabilization, degradation fragments of full-length peptides occurred in the fresh frozen tissues. The sample preparation protocols were furthermore tested on rat brains affected by acute anesthesia induced by isoflurane and medetomidine, showing comparable results to non-anesthetized animals on the neurotransmitters level without significant changes. Our data provide evidence for the potential use of heat stabilization prior to MALDI-MSI analyses to improve the examination of the in vivo state of neuronal chemical messengers in brain tissues not impacted by prior acute anesthesia.
Keywords: metabolites; Male; Freezing; neurotransmitter; brain; potkani Sprague-Dawley; Brain; neurotransmiterové látky; neuropeptide; postmortem degradation; mužské pohlaví; neurony; mass spectrometry imaging; krysa rodu Rattus; zmrazování; Neurotransmitter Agents; Animals; zvířata; Neurons; Rats; vysoká teplota; mozek - chemie; mozek; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Brain Chemistry; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Hot Temperature; Rats, Sprague-Dawley